Kinematic differences in forehand serve-receiving techniques of the male tennis players at low and high-speed serves - Yuxin Zhang; Zhouye Chen (Scientific Reports, 2024)
Abstract The purpose of this study was to compare the joint, racket, and ball kinematics between the different levels of male tennis players in tennis serve-return at slow and high serve speeds. Thirty male tennis players were divided into an advanced group (n = 15) and an intermediate group (n = 15) based on skill level. The advanced group and intermediate group matched shake hand-grip players performed serve-receive test at the different serve speeds. Kinematic data were collected on the trunk, upper limbs, racket and ball to compare the differences between the advanced and intermediate groups at different serve speeds. At both serve speeds, the AG has faster racket speed and ball speed, and is closer to the baseline placement (p<0.05). It is characterized by a faster trunk turn, greater speed with the shoulder joint forward and outward and greater angle of wrist flexion and extension during the stroke (p<0.05), and greater speed with the forearm inward and internal rotation during the follow-through swing, at the same time, there is a difference in the angle of the racket to the ground between the advanced group and an intermediate group(p<0.05). Elbow internal rotation and abduction angular velocity in the backswing phase, Timing of peak racket resultant velocity and Wrist extension in the stroke phase, and shoulder and elbow joint activities in the follow-through phase were significantly correlated with the ball speed of the return. With faster serve speeds, higher quality serve-receive can be achieved by shortening the duration of the backswing lifting the upper arm and rotating the forearm inward quickly, accelerating the speed of movement of wrist joints at the impact phase, adjusting the speed of shoulder adduction and elbow internal rotation to complete the follow-through swing. These findings help to improve elite players’ serve-receive skills at faster serve speed.